Modulating Ion Diffusivity and Electrode Conductivity of Carbon Nanotube@Mesoporous Carbon Fibers for High Performance Aluminum–Selenium Batteries. Issue 51 (14th November 2019) - Kong, Yueqi; Nanjundan, Ashok Kumar; Liu, Yang; Song, Hao; Huang, Xiaodan; Yu, Chengzhong
Abstract: Selenium (Se)‐based rechargeable aluminum batteries (RABs), known as aluminum–selenium (Al–Se) batteries, are an appealing new battery design that holds great promise for addressing the low‐capacity problem of current RAB technology. However, their applications are hindered by mediocre high‐rate capacity (≈100 mAh g −1 at 0.5 A g −1 ) and insufficient cycling life (50 cycles). Herein, the synthesis of mesoporous carbon fibers (MCFs) by coating mesoporous carbon with short‐length mesopores and tunable mesopore sizes (2.7 to 8.9 nm) coaxially on carbon nanotubes (CNT) is reported. When compositing MCFs with Se for Al–Se batteries, a positive correlation between mesopore size and electrolyte ion diffusivity is observed, however when pore size is increased to 8.9 nm, large voids are created at the interface of CNT core and mesoporous carbon shell, leading to decreased electrode conductivity. The trade‐off between ion diffusivity and interfacial connectivity/conductivity determines MCF with pore size of 7.1 nm as the best host material for Al–Se batteries. The composite cathode delivers high specific capacities (366 and 230 mAh g −1 at 0.5 and 1 A g −1 ), good rate performance, and excellent cycling stability (152 mAh g −1 after 500 cycles at 2 A g −1 ), superior over previously reported Se cathodes and other cathodes for RABs. Abstract : Mesoporous carbon fibers (MCFs) with finely modulated ion diffusion property and electrochemical conductivity are developed for high performance Al–Se batteries. These materials are synthesized by coaxially coating mesoporous carbon with tunable mesopore sizes on carbon nanotubes. The trade‐off between electrolyte ion diffusivity and electrode conductivity determines MCF with 7.1 nm pores as the best host material for Al–Se batteries.